Dinamika Permasalahan Masyarakat Perbatasan Indonesia – Timor Leste: Menyikapi Lintas Batas Negara - Ratnaduhita, Cintya; Puryanti, Lina; Husain, Sarkawi B. (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2025)
The border area between Indonesia and Timor Leste in East Nusa Tenggara exhibits complex social, economic, and cultural dynamics that rely heavily on cross-border activities facilitated by the Border Pass (PLB) and Border Crossing Identification Card (KILB). The COVID-19 pandemic temporarily halted these activities, disrupting trade, social relations, and the economic well-being of border communities. This study aims to examine the role of PLB and KILB in the lives of people living along the Indonesia–Timor Leste border. The research adopts a qualitative approach using a literature review method presented descriptively. The findings indicate that the restriction of cross-border mobility led to limited access in maintaining family ties, practicing cultural traditions, and engaging in economic activities. Communities experienced a sense of loss in their daily social interactions. Within the framework of cultural constructivism, social interactions and legal frameworks shape a culture that influences identity and cross-border relationships. Therefore, restoring mobility and the functions of PLB/KILB is essential for post-pandemic cultural reconstruction and for strengthening the social ties and identity of border communities.